Application of gas chromatography with tandem mass spectrometry for certification of the reference material of «Dioxins» in animal fat - A. I. Krylov; A. Y. Mikheeva; A. G. Budko (Стандартные образцы, 2020)
The article presents the results of applying gas chromatography - mass-spectrometry (GC-MS) and tandem mass spec-trometry (GC-MS/MS) methods for determination of certified values (mass fraction) of «Dioxins» - Polychlorinated Dibenzo-p-dioxins and Dibenzofurans (PCDD/PCDF) in animal fat. It has been established that the using of tandem mass-spectrometry makes it possible to reduce the Limit of Detection and Limit of Quantification of the congeners an order of magnitude and also it significantly improves the accuracy of the CRM. As a result, the certified values of PCDF congeners were determined in the range from 0,5 to 850 ng/kg and PCDD congeners in the range from 0,5 to 2 ng/kg. The relative expanded uncertainty of the certified values by using the GC-MS/MS does not exceed 7 %. Thus, the CRM of PCDD/PCDF in animal fat was developed for the purpose of validation, verification of measurement procedures and quality control of measurement results.